First International Meeting of Tropical Medicine Institutes, Lima, June 12-14, 2013 - Alarcón, Jorge O. (2014)
The First International Meeting of Institutes of Tropical Medicine, held in Lima, was the main event of the 50th anniversary of the establishment of the Institute of Tropical Medicine Daniel A. Carrion (1963-2013), Faculty of Medicine at UNMSM. The major Peruvian scientific institutions for research and management of global health burdens affecting tropical and subtropical regions participated in the organization of this event. About one thousand people attended. Topics included child health in the tropics, international health, HIV/AIDS, dengue, malaria, leishmaniasis, tuberculosis, Carrion's disease and emerging diseases. Representatives of the nine institutes of Tropical Medicine of the region who attended the event signed a declaration in which all represented institutes agreed to promote in their respective countries the recommendations of the World Health Assembly and the Pan American Health Organization in relation to neglected diseases, health research and health human resources; to develop regional graduate programs in tropical medicine, epidemiology and public health; to coordinate the activities of this meeting with other regional and subregional initiatives. The declaration also decreed, among other topics, that the participating institutes will hold the Second International Meeting of Institutes of Tropical Medicine in two years.